2021
DOI: 10.1093/icesjms/fsaa165
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and body size affect recruitment and survival of sandeel across the North Sea

Abstract: Climate effects on marine fish depend on life stage, particularly when life stages differ in habitat utilization. In the present study, we investigated life stage-dependent responses of lesser sandeel (Ammodytes marinus) to temperature at contrasting geographical scales. We related population density and individual growth to temperature and found different temperature responses between the first and the second years of life. During the first year of life, fish size was the single most important factor influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 96 publications
(135 reference statements)
0
7
0
Order By: Relevance
“…Although, initial investigations leading to the current study explored the latter (Henriksen, 2020), it was considered outside the framework of this paper. In support of the bioenergetics hypothesis, previous studies have demonstrated relationships between recruitment survival and size of age 0 fish (Foy & Paul, 1999; Henriksen et al, 2021), and both theoretical and experimental work have demonstrated accelerated reserve depletion during warm winters (van Deurs, Hartvig, et al, 2011; Wright et al, 2017).…”
Section: Discussionmentioning
confidence: 82%
“…Although, initial investigations leading to the current study explored the latter (Henriksen, 2020), it was considered outside the framework of this paper. In support of the bioenergetics hypothesis, previous studies have demonstrated relationships between recruitment survival and size of age 0 fish (Foy & Paul, 1999; Henriksen et al, 2021), and both theoretical and experimental work have demonstrated accelerated reserve depletion during warm winters (van Deurs, Hartvig, et al, 2011; Wright et al, 2017).…”
Section: Discussionmentioning
confidence: 82%
“…Abundances vary throughout the foraging season which would account for the dietary plasticity exhibited by these whales (Robinson et al, 2023). Sandeels were most abundant during June and July, when they are foraging in the water column, but declined from August onwards, when they return to burrows in the sediment (Henriksen et al, 2021) (Figure 2.5). Meanwhile, clupeids were most abundant in June and September.…”
Section: Minke Whale Habitat Use In Relation To Prey Speciesmentioning
confidence: 99%
“…These schools form bridging structures that likely play an important role in their ecology and prevent post‐settled juveniles from being disconnected from suitable bottom substrate 22 . The strong selectivity for areas with specific granulometry represents a habitat limitation that increases the vulnerability of the sandeel to climate change, high fishing pressure, and anthropogenic activity that degrades or eliminates their habitat 10,22‐26 …”
Section: Introductionmentioning
confidence: 99%
“…22 The strong selectivity for areas with specific granulometry represents a habitat limitation that increases the vulnerability of the sandeel to climate change, high fishing pressure, and anthropogenic activity that degrades or eliminates their habitat. 10,[22][23][24][25][26] These specific sandy habitats are also important for the early life stages of sandeel because they spawn a single batch of demersal eggs that adheres to the sand in an oxygen-rich environment. [24][25][26] After a long (1 month) embryonic period, larvae hatch and drift with the current in the deep layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation